Construction 3D BIM-based knowledge management system: a case study - Lin, Yu-Cheng (Journal of Civil Engineering and Management, 2014)
Knowledge management (KM) is the organization, creation, sharing and flow of knowledge within organizations. Knowledge can be shared and reused among involved engineers and experts to improve a construction process and reduce the time and cost of solving problems. This paper proposes a new and practical methodology to capture and represent construction project knowledge by using a Building Information Modeling (BIM) approach. Using BIM approach, users can make visual knowledge management in the 3D Computer-aided Design (CAD) environment. This study addresses the application of knowledge management in the construction phase of construction projects and proposes a Construction BIM-based Knowledge Management (CBIMKM) system for general contractors. The CBIMKM is then applied in selected case studies of a construction building project in Taiwan to verify our proposed methodology and demonstrate the effectiveness of sharing knowledge in the 3D environment. By applying the BIM approach, all participants in a project can share and reuse explicit and tacit knowledge through the 3D CAD-based knowledge map. The combined results demonstrate that the CBIMKM system can be used as a visual 3D-based knowledge management platform by utilizing the BIM approach and web technology.